2020
DOI: 10.3390/opt1020016
|View full text |Cite
|
Sign up to set email alerts
|

A Miniature pH Probe Using Functional Microfiber Bragg Grating

Abstract: Operando and precisely probing aqueous pH is fundamentally demanded, both in chemical and biological areas. Conventional pH probes, subjected to the larger size, are probably unfit for application in some extreme scenarios, such as a trace amount of samples. In this paper, we have further developed the pH sensor that leverages the microfiber Bragg grating with an ultra-compact size down to an order of magnitude of 10−14 m3. Using the electrostatic self-assembly layer-by-layer technique, the functional film con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…It can be, thus, concluded that the PANI/Pt-coated FO-SPR sensor provides a linear SPR response on the entire pH range, and that the observed pH response is mainly attributed to the sensitive RI changes of the PANI film, as the RI value of the pH solutions is maintained constant throughout the measurements [ 7 , 29 ]. In particular, in respect to the neutral pH value (7), it was observed that increasing the pH triggers a SPR wavelength shift towards lower wavelengths, whilst, oppositely, decreasing the pH determines a SPR wavelength shift towards higher wavelengths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be, thus, concluded that the PANI/Pt-coated FO-SPR sensor provides a linear SPR response on the entire pH range, and that the observed pH response is mainly attributed to the sensitive RI changes of the PANI film, as the RI value of the pH solutions is maintained constant throughout the measurements [ 7 , 29 ]. In particular, in respect to the neutral pH value (7), it was observed that increasing the pH triggers a SPR wavelength shift towards lower wavelengths, whilst, oppositely, decreasing the pH determines a SPR wavelength shift towards higher wavelengths.…”
Section: Resultsmentioning
confidence: 99%
“…Accurate pH values of each solution were determined with a Consort C1010 pH-meter with a resolution of pH. As reported elsewhere, the reagents used for preparing the pH analyzing media have been specifically selected to minimize the potential disturbances caused by the RI variation of the pH solutions [ 7 , 29 ]. Their RI units were thus verified with the digital refractometer, and the measured value of ∼1.334 (closed to the typical RI value of DIW, i.e., ) was considered constant among the pH solutions, as it lied within the resolution of the digital refractometer.…”
Section: Methodsmentioning
confidence: 99%
“…Penelitian berbasis sensor serat optik semakin banyak diminati peneliti karena memiliki kemampuan untuk memantau berbagai variable lingkungan seperti kelembaban, kekeruhan, tekanan, suhu, pH, dan lain-lain. Variable-variabel tersebut sangat erat kaitannya dengan sifat dari air [7]- [14].…”
Section: Pendahuluanunclassified
“…Optical fiber has the advantages of anti-electromagnetic interference, corrosion resistance, small size, low price [1], and fiber Bragg gratings (FBGs) have not only these advantages, but also the function of multiplexing, which are widely used in temperature [2][3][4][5], humidity [6,7], gas [8], wind direction [9] and stress [10][11][12] sensing fields. However, ordinary FBG is not sensitive to the change of external refractive index, so people turn to the research of MFBG, and successfully developed many kinds of sensors with high sensitivity, such as refractive index sensor [13][14][15][16], temperature sensor [17,18], gas sensor [19,20], biosensor [21], PH sensor [22], stress sensor [23], humidity sensor [24] and so on. MFBGs are mainly fabricated by chemical etching [25], 3D printing [26], fused biconical taper first and further processing (include focused ion beam milling [27,28], laser irradiation [29][30][31], UV irradiation [18,24].…”
Section: Introductionmentioning
confidence: 99%